2019
DOI: 10.1016/j.srhc.2019.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Offering weight management support to pregnant women with high body mass index: A qualitative study with midwives

Abstract: Offering weight management support to pregnant women with high body mass index: a qualitative study with midwives

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…In line with previous research, participants were generally supportive of health professionals raising issues such as maternal weight and pregnancy weight gain [25,26,74,82,83] and to child growth/weight [29], even if they would be hard to hear, if done in a non-judgemental, supportive way. Continuity of care, and the associated development of trusting, respectful relationships and rapport with health professionals, were highly valued by parents in this study, similar to prior research concerning antenatal care [74], weight and/or gestational weight gain [84][85][86], and infant feeding [47,64]. Thus, parents desire more support and for health professionals-with whom they have good rapport with-to be more pro-active in raising such issues.…”
Section: Discussionsupporting
confidence: 77%
“…In line with previous research, participants were generally supportive of health professionals raising issues such as maternal weight and pregnancy weight gain [25,26,74,82,83] and to child growth/weight [29], even if they would be hard to hear, if done in a non-judgemental, supportive way. Continuity of care, and the associated development of trusting, respectful relationships and rapport with health professionals, were highly valued by parents in this study, similar to prior research concerning antenatal care [74], weight and/or gestational weight gain [84][85][86], and infant feeding [47,64]. Thus, parents desire more support and for health professionals-with whom they have good rapport with-to be more pro-active in raising such issues.…”
Section: Discussionsupporting
confidence: 77%
“…Unfortunately, education sessions with other major referring staff were unable to be delivered which may explain the more successful attendance rates with midwife referrals. However, evidence also suggests that midwives build a relationship with women prior to discussing weight, and are central to supporting women with weight management during pregnancy . Smoking during pregnancy, and in general, has been linked with lower health literacy which may explain their lower attendance to dietitian appointments .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding weight management opportunities, public health nurses described a lack of resources as the reason counseling and support were missing after birth and weight-management was not part of standard care [30,7]. Resources should be added postnatally for overweight women to facilitate personalized counseling [31].…”
Section: Discussionmentioning
confidence: 99%
“…We found that one of the important aspects of weight management was support from partners and family. Women's partners play a signi cant role in providing advice and are seen as invaluable support [7]. In addition, women described how their family, relatives, friends, and health care professionals in uenced, for example, healthy food choices [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation